A cohort study examining urgent and emergency treatment for decompensated severe aortic stenosis. Issue 2 (February 2021) - Ali, Noman; Patel, Peysh; Wahab, Ali; Das, Arka; Blackman, Daniel J.; Cunnington, Michael S.; Malkin, Christopher J.
Abstract : Aims: We compared strategies in the treatment of decompensated severe aortic stenosis. The hypothesis was that undertaking urgent or emergency transcatheter aortic valve implantation (TAVI) directly in such patients is safer and more effective than urgent or emergency balloon aortic valvuloplasty (BAV) followed by elective TAVI or surgical aortic valve replacement (SAVR). Methods: This was a single-centre retrospective study including all consecutive patients who underwent urgent or emergency BAV or TAVI for decompensated severe aortic stenosis between September 2014 and February 2018. Primary endpoints were 30-day and 1-year mortality. Results: Fifty-two patients underwent urgent or emergency BAV and 87 underwent TAVI. Baseline characteristics of the two groups were well matched. Significant differences were noted between the two groups in 30-day all-cause mortality (88.5% BAV patients alive at 30 days, 97.7% TAVI patients; P  < 0.05) and 1-year all-cause mortality (44.2% BAV patients alive at 1 year, 88.5% TAVI patients; P  < 0.001). At 1 year, the estimated hazard ratio for patients undergoing BAV was 11.2 (95% confidence interval: 4.67–26.9; P  < 0.001) when adjusted for potential confounding variables. Patients in the BAV group who successfully underwent subsequent TAVI or SAVR all survived for 365 days, but there was no significant 1-year mortality difference compared with those who underwent urgent or emergency TAVI (100 vs. 88.5%; P  > 0.155). Conclusion: Our results suggest treatment of decompensated severe aortic stenosis with urgent or emergency TAVI may be associated with improved survival outcomes when compared with a strategy of performing BAV as a bridge to subsequent TAVI or SAVR.